Transcriptome Analysis of Skeletal Muscle Reveals Altered Proteolytic and Neuromuscular Junction Associated Gene Expressions in a Mouse Model of Cerebral Ischemic Stroke - Ferrandi, Peter J. (Genes (Basel), 2020)
Stroke is a leading cause of mortality and long-term disability in patients worldwide. Skeletal muscle is the primary systemic target organ of stroke that induces muscle wasting and weakness, which predominantly contribute to functional disability in stroke patients. Currently, no pharmacological drug is available to treat post-stroke muscle morbidities as the mechanisms underlying post-stroke muscle wasting remain poorly understood. To understand the stroke-mediated molecular changes occurring at the transcriptional level in skeletal muscle, the gene expression profiles and enrichment pathways were explored in a mouse model of cerebral ischemic stroke via high-throughput RNA sequencing and extensive bioinformatic analyses. RNA-seq revealed that the elevated muscle atrophy observed in response to stroke was associated with the altered expression of genes involved in proteolysis, cell cycle, extracellular matrix remodeling, and the neuromuscular junction (NMJ). These data suggest that stroke primarily targets muscle protein degradation and NMJ pathway proteins to induce muscle atrophy. Collectively, we for the first time have found a novel genome-wide transcriptome signature of post-stroke skeletal muscle in mice. Our study will provide critical information to further elucidate specific gene(s) and pathway(s) that can be targeted to mitigate accountable for post-stroke muscle atrophy and related weakness.